Deactivation and regeneration dynamics in hierarchical zeolites: Coke characterization and impact on catalytic cracking of vacuum gas oil - Fals Guerra, Jayson (2024)
This study investigated the deactivation and regeneration of hierarchical zeolites in vacuum gasoil conversion, aiming to reach the equilibrium state seen in fluidized bed catalytic cracking(FCC). The research utilized various characterization techniques to analyze the properties ofzeolites before and after coking and regeneration. Zeolite Y-0.20-S was found to have the highestgasoline selectivity and quality, mirroring industrial yields, and displayed notable stability acrossdeactivation/regeneration cycles. Higher mesopore concentration in zeolites led to increased cokeselectivity and better resistance to deactivation. The study observed a dominance of aromaticcoke with a higher degree of condensation in these zeolites. Despite coke deposition affecting acidand textural properties, the regeneration process effectively restored these characteristics,proving its efficiency. The zeolites with greater mesoporosity retained their fundamental properties responsible for activity and selectivity, highlighting the importance of selecting materialsthat provide high conversions and maintain stability and product selectivity over multiple cycles.The Y-0.20-S zeolite, in particular, was identified as a promising candidate for commercialcatalyst development for gasoline production, contributing to the FCC process’s energy efficiency.